Reconquest and crusade in medieval Spain - O'Callaghan, Joseph F. (The Middle Ages series, 2003)
Drawing from both Christian and Islamic sources, Reconquest and Crusade in Medieval Spain demonstrates that the clash of arms between Christians and Muslims in the Iberian peninsula that began in the early eighth century was transformed into a crusade by the papacy during the twelfth and thirteenth centuries. Successive popes accorded to Christian warriors willing to participate in the peninsular wars against Islam the same crusading benefits offered to those going to the Holy Land. Joseph F. O'Callaghan clearly demonstrates that any study of the history of the crusades must take a broader view of the Mediterranean to include medieval Spain. Following a chronological overview of crusading in the Iberian peninsula from the late eleventh to the middle of the thirteenth century, O'Callaghan proceeds to the study of warfare, military finance, and the liturgy of reconquest and crusading. He concludes his book with a consideration of the later stages of reconquest and crusade up to and including the fall of Granada in 1492, while noting that the spiritual benefits of crusading bulls were still offered to the Spanish until the Second Vatican Council of 1963. Although the conflict described in this book occurred more than eight hundred years ago, recent events remind the world that the intensity of belief, rhetoric, and action that gave birth to crusade, holy war, and jihad remains a powerful force in the twenty-first century.